Determinants of inbound international tourism from USA, Japan and Korea - Bautista, Ria G. (Animo Repository, 2005)
Tourism is an umbrella concept for the reason that there may be different ideas and perceptions regarding tourism. Tourism, as defined by the World Tourism Organization is something that comprises the activities of persons traveling and staying places outside their usual environment not exceeding one consecutive year for leisure, business and other purposes not related to the exercise of an activity with compensation. Inbound tourism, which the researchers will be focusing on, involves non-residents of an economy traveling within the economy of compilation. The top three countries according to tourist arrivals in the Philippines are United States of America, Japan and Korea, respectively, accounted for more than half of the total international tourism in the Philippines. Tourism is powerful and an efficient industry that is often neglected. Through this powerful and efficient industry, the Philippines can accommodate high levels of investments, it can have a very high value added retention rate, it can generate employment and high foreign investments and since the tourism industry is global in size, it can have strong growth potential. Through the extraction of particular tourism demand models for each of the top three countries that generate tourist arrivals in the Philippines, factors which were important for the tourists in their decision to travel and the seasonality of tourism demand of each country were obtained, all of which could facilitate in developing the Philippine tourism sector.